2021
DOI: 10.3389/fcimb.2021.737364
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-Derived Suppressor Cells in Trypanosoma cruzi Infection

Abstract: Myeloid-derived suppressor cells (MDSCs) are immature heterogeneous myeloid cells that expand in pathologic conditions as cancer, trauma, and infection. Although characterization of MDSCs is continuously revisited, the best feature is their suppressor activity. There are many markers for MDSC identification, it is distinctive that they express inducible nitric oxide synthase (iNOS) and arginase 1, which can mediate immune suppression. MDSCs can have a medullary origin as a result of emergency myelopoiesis, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 126 publications
0
5
0
Order By: Relevance
“…Interestingly, in both spleen and heart of T. cruzi-infected mice, infiltrating MDSCs coexpress iNOS and arginase-1 and suppress T cell proliferation . We do not discard the possibility that these cells may also be present in the aorta of T.cruzi-infected mice.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Interestingly, in both spleen and heart of T. cruzi-infected mice, infiltrating MDSCs coexpress iNOS and arginase-1 and suppress T cell proliferation . We do not discard the possibility that these cells may also be present in the aorta of T.cruzi-infected mice.…”
Section: Resultsmentioning
confidence: 87%
“…In addition to inflammatory infiltrate, it has been reported that during T. cruzi infection, myeloid-derived suppressor cells (MDSCs) infiltrate the heart and mediate the myocarditis . Interestingly, in both spleen and heart of T.…”
Section: Resultsmentioning
confidence: 99%
“…NOS2, the gene for inducible Nitric Oxide Synthase (iNOS), is a key signaling molecule in the induction of NO. NO has been shown to have both beneficial and detrimental effects on T. cruzi infection ( Fresno and Gironès, 2021 ). NO activates macrophage-killing mechanisms and can be protective against T. cruzi infection ( Muñoz-Fernández et al, 1992 ; Lee et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, mice defective in iNOS signaling are unable to control T. cruzi parasite burdens and succumb to infection ( Hölscher et al, 1998 ). However, it has also been shown that myeloid-derived suppressor CD11b+Ly6C+Ly6G lo cells (MDSC) are present in the spleens and hearts of T. cruzi -infected mice, they express iNOS and Arg1, and they induce expansion of Foxp3-expressing regulatory T cells ( Huang et al, 2006 ; Fresno and Gironès, 2021 ). Further, induction of NO by iNOS interferes with IL-2R signaling and alters the stability of IL-2 mRNA ( Bronte and Zanovello, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…These suppressor cells derived from the myeloid line (MDSC) are characterized by a group of heterogeneous cells that have the ability to inhibit the activity of cells through mechanisms associated with the production of reactive oxygen species (ROS), expression of arginase 1 (ARG1) and inducible nitric oxide synthase (iNOS), and the presence of immunosuppressive cytokines ( Medina and Hartl, 2018 ). Studies in mice have shown the importance of MDSCs in the infection control as well as and their future application in the development of immunotherapeutic measures against T. cruzi ( Fresno and Gironès, 2021 ). Therefore, we are analysing MDSCs in patients with different stages of the disease to determine their role in human Chagas disease.…”
Section: Perspectivesmentioning
confidence: 99%